Demand for Imports in Venezuela : A Structural Time Series Approach - Cuevas, Mario A. (World Bank, Washington, D.C., 2013)
Using structural time series models, Cuevas estimates common stochastic trends of real GDP and imports in Venezuela from 1974-2000. The real imports trend drifts upward at almost twice the rate of growth of GDP. This highlights the powerful structural tendency toward increasing imports in Venezuela. The author also explicitly estimates common stochastic cycles, which he finds to have 5 and 17 year periods. In addition, he finds that a 1 percent real exchange rate appreciation leads to a 0.4 percent increase in imports. And in the long-run, 1 percent real GDP growth is associated with 1.7 percent real imports growth. The author also shows that the GDP elasticity of imports uniformly falls with cycle period, with the elasticity reaching 4.55 at the frequency associated with the 5-year cycle. A powerful imports responsiveness at the higher cycle frequency is associated with the recurrence of external imbalances in Venezuela.